The Potential Role of Contraction-Induced Myokines in the Regulation of Metabolic Function for the Prevention and Treatment of Type 2 Diabetes - Carson, Brian P. (Frontiers in Endocrinology, 2017)
Skeletal muscle represents the largest organ in the body and has recently been recognised as having an endocrine function. Proteins expressed and released by muscle that have auto-, para- and endo-crine bioactivities have been termed myokines. It is likely that muscle contraction represents the primary stimulus for the synthesis and secretion of myokines to enable communication with other organs such as the liver, adipose tissue, brain and auto-regulation of muscle metabolism. To date, several hundred myokines in the muscle secretome have been identified, a sub population of which are specifically induced by skeletal muscle contraction. However, the bioactivity of many of these myokines and the mechanism through which they act has either not yet been characterised, or remains poorly understood. Physical activity and exercise are recognised as a central tenet in both the prevention and treatment of Type 2 Diabetes. Recent data suggest humoral factors such as muscle-derived secretory proteins may mediate the beneficial effects of exercise in the treatment of metabolic diseases. This mini review aims to summarise our current knowledge on the role of contraction-induced myokines in mediating the beneficial effects of physical activity and exercise in the prevention and treatment of Type 2 Diabetes, specifically glucose and lipid metabolism. Future directions as to how we can optimise contraction-induced myokine secretion to inform exercise protocols for the prevention and treatment of Type 2 Diabetes will also be discussed.